Synthesis and Structural Analysis of Powder Complex of Tris(bipyridine)cobalt(II) Trifluoromethanesulfonate Octahydrate - Kristian Handoyo Sugiyarto; Cahyorini Kusumawardani; Kristanti Eka Wulandari (Universitas Gadjah Mada, 2018)
The powder complex of tris(bipyridine)cobalt(II) trifluoromethanesulfonate octahydrate has been synthesized by direct interaction of the corresponding aqueous solutions (and drops of ethanol) of cobalt(II) nitrate, bipyridine, and potassium triflate. The yellow-orange powder produced was filtered off and allowed to dry on an aeration for characterization. AAS measurement showed the content of metal to be 6.06%, corresponding to the theoretical value of 6.06% in [Co(bipy)3](CF3SO3)2.8H2O. The analysis of conductance producing the charge ratio of cation to anion to be 2:1, confirms the formula. The magnetic moment, µeff, of this complex which was to be 4.5-4.9 BM, indicates that the complex is paramagnetic corresponding to the three unpaired electrons with a significantly orbital contribution. UV-Vis spectrum of the complex reveals the first band observed at about 11100 cm–1, which is associated with the spin-allowed transition, 4T1g → 4T2g. A distinct shoulder at only about 16100 cm–1 should be associated with the spin-forbidden transition of 4T1g → 2T2g,2T2g (G). The expected second and third bands which are associated with spin-allowed transitions of 4T1g → 4T1g(P) and 4T1g → 4A2g at higher energy were not well resolved. The infrared spectrum shows absorptions of the functional group of ligand which is influenced by the metal-ligand interaction in this complex. The powder XRD of this complex was refined using Le Bail method of Rietica program and found to be fit as monoclinic symmetry with a space group of C2/c.